Different forms of pulmonary hypertension in a family with clinical and genetic evidence for hereditary hemorrhagic teleangectasia type 2. (1st June 2018) - Greco, Alessandra; Plumitallo, Sara; Scelsi, Laura; Maggi, Giannantonio; Sobrero, Matteo; Turco, Annalisa; Raineri, Claudia; Arseni, Natalia; Cappelletti, Donata; Visconti, Luigi Oltrona; Pagella, Fabio; Spinozzi, Giuseppe; et al.
Abstract : Hereditary hemorrhagic telangiectasia (HTT) is an autosomal dominant disease, most frequently caused by a mutation in either ENG or ACVRL1, which can be associated with pulmonary arterial hypertension (PAH). In this report, we describe a new unpublished ACVRL1 mutation segregating in three members of the same family, showing three different types of pulmonary hypertension (PH) in the absence of BMPR2 mutations. The first patient has a form of heritable PAH (HPAH) in the absence of hepatic arteriovenous malformations (AVMs); the second one has a severe form of portopulmonary hypertension (PoPAH) associated with multiple hepatic AVMs; the third one has hepatopulmonary syndrome (HPS) with numerous hepatic arteriovenous fistulas and a form of post‐capillary PH due to high cardiac output. In summary, a single mutation in the ACVRL1 gene can be associated, in the same family, with an extreme phenotypic variability regarding not only the clinical presentation of HHT but also the type of PH in the absence of BMPR2 mutations. More studies are needed to evaluate if this variability can be explained by the presence of additional variants in other genes relevant for the pathogenesis of HHT.